A study on Dengue infection, seroprevalence and its seasonal distribution among patients attending a Tertiary Care Hospital, Kanchipuram, India - Kamalraj Mohan, Senthamarai Srinivasan, Sivasankari Selvaraj, Arumugam Suresh, Akila Krishnamoorthy (Journal of Applied Pharmaceutical Science, 2025)
Dengue fever, an acute arboviral disease transmitted by Aedes mosquitoes, poses a serious and potentially fatal threat to humans. Increasing urbanization and changing climatic conditions have led to a progressive increase in dengue cases worldwide. This current study was done to elucidate the seroprevalence and incidence of dengue virus (DENV) in patients admitted to a healthcare facility in India. The study was conducted at Meenakshi Medical College Hospital and Research Institute, Kanchipuram, India, from January 2022 to 2023. Over the course of 13 months, blood samples were collected from individuals suspected of having dengue and analyzed for dengue markers NS1 Ag, IgM, and IgG antibodies using the MAC-ELISA method. Of the 416 suspected cases, 102 (25%) had a positive result for DENV infection, with a higher incidence in men (54%) than in women (45%). Predominant cases were found in the age group 16–30 years (34.3%), then at 1–15 years (21.5%). Among the seropositive, 55.3% indicated a recent primary infection. In terms of temporal distribution, dengue cases occurred predominantly after the monsoon, particularly in November (27.4%) and October (17.4%). The importance of dengue in research on climate-related infectious diseases underscores its importance. Timely identification, continuous surveillance, and supportive measures are critical to mitigating the severity and mortality of dengue cases.
Keywords: Dengue infection, seroprevalence, seasonal distribution